Writing wrongs: Implications of Foucauldian theory for researching racism discourse - Elizabeth Carriere (Adult Education Research Conference, 1993)
The author investigated how theoretical and analytical aspects of Foucauldian poststructuralism might contribute to understanding contemporary meanings of racism. In particular, discourse analysis is examined as an interpretive framework for "reading" theoretical accounts of racism.